Iconic Meanings of Flora Names in Dipasena as the Shrimp Aquaculture Area: Envirolinguistic Study - Listiani, Fransisca Despa; Rahardi, R. Kunjana (English Department FBS UNP, 2020)
This paper aims to expose aspects and shapes of iconic meanings of flora names in Dipasena as the shrimp aquaculture area and describe the relationship between the shape and meaning of its icon.Â This type of research is naturalistic qualitative. The results of the study include the following things. (1) rubber tree-fire gum has a similarity with the flame. (2) The Berembang tree has fruit that is shaped like a flagpole or the dome of the mosque. (3) The characteristic of Waru doyong tree trunk that tends to grow inclined is likened to the meaning of the term doyong in bahasa Indonesia. (4) The shape of the leaf perumpungan similar to the shape of small sheep ears. (5) There is a similarity of sound between the name of the Pletekan flower with the sound produced by the eruption of the fruit. (6) There is a similarity between banana Muli and muli (girl in bahasa Lampung). (7) There are similarities of silk moss with silk yarn. (8) There is a similarity between intestinal moss and chicken intestines. From the results of the study can be concluded that the names of the flora have an iconic meaning and not arbitrary.